2010
DOI: 10.1186/1471-2377-10-117
|View full text |Cite
|
Sign up to set email alerts
|

Severe course of Lyme neuroborreliosis in an HIV-1 positive patient; case report and review of the literature

Abstract: BackgroundLyme Neuroborreliosis (LNB) in a human immunodeficiency virus (HIV) positive patient is a rare co-infection and has only been reported four times in literature. No case of an HIV patient with a meningoencephalitis due to LNB in combination with HIV has been described to date.Case presentationA 51 year old woman previously diagnosed with HIV presented with an atypical and severe LNB. Diagnosis was made evident by several microbiological techniques. Biochemical and microbiological recovery during treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
(25 reference statements)
0
12
0
1
Order By: Relevance
“…Till now studies investigating the epidemiology of tick-borne pathogen infection have focused on healthy individuals with normal immunological function and living in endemic regions or clinical findings among hospitalized patients. In HIV-positive patients, where a serological diagnosis is complicated due to reduced positive predictive value, a method where the microorganism detected directly might be of great value [ 11 ]. Hence, we conducted a retrospective, molecular study to ascertain the prevalence and incidence of tick-borne infections in HIV-infected persons with no clinical symptoms located in Poland, an endemic area for I. ricinus ticks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Till now studies investigating the epidemiology of tick-borne pathogen infection have focused on healthy individuals with normal immunological function and living in endemic regions or clinical findings among hospitalized patients. In HIV-positive patients, where a serological diagnosis is complicated due to reduced positive predictive value, a method where the microorganism detected directly might be of great value [ 11 ]. Hence, we conducted a retrospective, molecular study to ascertain the prevalence and incidence of tick-borne infections in HIV-infected persons with no clinical symptoms located in Poland, an endemic area for I. ricinus ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high incidence of HIV, co-infection with B. burgdorferi is rarely reported in medical journals [ 11 , 12 ]. The vast majority of cases involve typical Lyme neuroboreliosis symptoms, such as meningoradiculitis and facial palsy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, our data showed that patients with HIV almost exclusively developed LD subsequent to the HIV diagnosis, suggesting that immune system alteration increases the risk of LD. A handful of case reports have indicated that HIV-positive immunocompromised patients develop more severe Lyme complications following infection [52][53][54] . Although the specific immunological mechanisms driving this connection remain unclear, it seems reasonable to speculate that immunosuppression plays an important role 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Los niños prematuros generalmente presentas deficiencias en las funciones cognitivas, lo que se ve reflejado en el rendimiento académico que es una medida de la capacidad de respuesta del individuo, es una estimación de lo que se ha aprendido a través de la enseñanza (Burgel, Oosterloo, Kroon & Dam, 2010) Durante la revisión de la literatura se han descrito de forma detallada las consecuencias que trae la prematurez para cada función cognitiva, lo que se ve reflejado directamente en aprendizaje durante la vida escolar, pues la afectación ya sea de la atención, la memoria, el lenguaje, las funciones ejecutivas, la conducta o la Teoría de la mente, es un indicador de posibles dificultades, pues un fallo en alguna de estas áreas podría desencadenar problemas mayores.…”
Section: Conducta Y Emociones En La Prematurezunclassified